Evaluasi Kolam Retensi Perumahan Bandung Inten Indah, Kelurahan Derwati, Kecamatan Rancasari, Kota Bandung - Selvia, Idza; Eka Wardhani; Iwan Juwana; Kancitra Pharmawati (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
This study aims to evaluate the performance of the initial retention pond design in the Bandung Inten Housing Complex and to plan for an increase in storage capacity based on the hydrological conditions of the area. The research method refers to the guidelines of the Directorate General of Human Settlements, which include hydrological analysis, determination of runoff discharge, preparation of inflow hydrographs, and calculation of pond storage volume. The evaluation results show that the initial retention pond with a volume 5.400 m3 is not yet capable of accommodating the planned runoff discharge. Based on the calculation results, the required pond volume is 7.509,42 m3 using a pump capacity of 0,03 m3/second, which is capable of reducing the runoff discharge in the Bandung Inten Housing Complex by 81,986%. However, additional alternative control measures are still needed to improve flood control effectiveness.